Current concepts in the diagnosis of ocular tuberculosis: A narrative review - Vinaya Kumar Konana; Kalpana Babu (Taiwan Journal of Ophthalmology, 2025)
Ocular tuberculosis (OTB) is one of the extrapulmonary manifestations caused by Mycobacterium tuberculosis (Mtb). If untreated, it can result in poor visual prognosis. Prompt diagnosis of OTB is met with challenges. The gold standard for the diagnosis of OTB is the direct demonstration of the Mtb in ocular tissues or ocular fluids either by Ziehl–Neelsen Stain, culture or molecular diagnostic techniques such as polymerase chain reaction. This is onerous owing to the paucibacillary nature of the disease, small quantity of samples, and low sensitivity and specificity of molecular diagnostic tests. Thus, one needs to rely on indirect evidences to make a diagnosis. Hence, most often, the diagnosis of OTB is presumed based on the geography the patient hails from and indirect laboratory evidences suggestive of TB. In this narrative review, we review clinical, laboratory, and radiology markers which aid in the diagnosis of OTB and outline the current concepts in the diagnosis of OTB.